Human Trafficking and the Crisis of Victim Protection in Indonesia - Therecya Angella Sitio; Hery Firmansyah (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
Human trafficking is a transnational crime that not only constitutes a serious violation of criminal law but also undermines the fundamental human rights and dignity of its victims. Although Indonesia has enacted Law No. 21 of 2007 on the Eradication of the Criminal Act of Trafficking in Persons, the implementation of victim protection remains constrained by various legal and institutional challenges. This study aims to examine the legal protection mechanisms available to victims of human trafficking and to identify the obstacles and strategies for optimizing such protection. Employing a normative legal research method, the study utilizes statutory, conceptual, and case-based approaches, with data analyzed qualitatively. The findings reveal that legal protection for victims encompasses restitution, rehabilitation, legal assistance, repatriation, and social reintegration. However, the implementation of these measures remains ineffective due to weak enforcement of restitution orders, limited rehabilitation facilities, and inadequate inter-agency coordination. Accordingly, strengthening preventive, repressive, and rehabilitative measures is essential through enhanced public awareness programs, improved cross-sectoral collaboration, expanded victim recovery services, and the utilization of technology-based support systems. These efforts are expected to promote a more effective, equitable, and victim-centered framework for legal protection and recovery.